Organizational Culture in Improving the Performance of State Civil Apparatus at the Minahasa Regency Education Office - Goinpeace H. Tumbel; Marthinus Mandagi; Einjelheart H. Polii; Miana D. Zalukhu; Rebeca Mowilos (Technium Social Sciences Journal, 2024)
This research aims to analyze and describe Organizational Culture in improving the performance of civil servants at the Education Office of Minahasa District. The research method used is descriptive qualitative, with 4 informants. Data collection involves observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The findings indicate that, based on the research, the performance improvement of civil servants in the Education Office of Minahasa District (Department of Elementary and Junior High School Development) has been successful due to the competence of the Head of Department in providing clear instructions, guiding staff through motivation, setting an example of exemplary behavior, imposing sanctions and warnings when necessary, and conducting supervision over the staff.